Comprehensive chemical characterization of lubricating oils used in modern vehicular engines utilizing GC × GC-TOFMS. (15th May 2018) - Liang, Zhirong; Chen, Longfei; Alam, Mohammed S.; Zeraati Rezaei, Soheil; Stark, Christopher; Xu, Hongming; Harrison, Roy M.
Graphical abstract: Highlights: Novel methodology developed to determine hydrocarbon composition. Straight, branched and cyclic alkanes quantified in lubricating oil. Fully synthetic, semi-synthetic, mineral and base oils characterised. Differences between fresh and used oils are quantified. Abstract: A number of major studies have demonstrated that the SVOC (Semi-volatile organic compounds) within engine emissions derive predominantly from unburned fuel and lubricants, and are a major contributor to primary atmospheric aerosol containing thousands of organic compounds. The GC × GC-ToF-MS (2 dimensional Gas Chromatography – Time of Flight – Mass Spectrometry) comprehensive analytical technique was utilized in this study, to resolve the complex mixtures and characterize the SVOC content in eight different commercial lubricants, including 5 W30 synthetic and semi-synthetic, mineral and base oil. In order to quantify the aliphatic isomers, which comprise the largest component of the lubricants, a TIC-M.Q./Mass (Total ion current ratio to the molar quantity/mass) method has been developed. The TIC intensity was observed to be proportional to the molar quantity of n-alkanes for carbon number 25, while being linear to the mass response for these aliphatic compounds with carbon number >C25 . Additionally, the TIC intensity of the alkyl-cyclohexanes under the identical retention indices were found to have an equivalent response to those of the n-alkanes, showing that the quantitative calibrations derived for the n-alkane series could be applied to estimate the concentrations of isomeric aliphatic compounds with similar molecular weight. Furthermore, a mesh method was introduced to group the alkane species (n-alkanes, branched alkanes and cyclic alkanes etc.), combining with the use of a soft EI (electron impact) ionization (14 eV) to retain the distinct identity of the isomers with less fragmentation, which allowed the TIC-M.Q./Mass methodology to integrate all the constitutional isomers present in the lubricating oil samples. By utilizing this methodology, compositions from different samples were comprehensively compared, leading to the following conclusions: 1) the synthetic and semi-synthetic oils contained a larger abundance of HMW (high molecular weight) aliphatic compounds (carbon number C24 –C29 ), while those in the LMW (low molecular weight range, carbon number C18 –C25 ) were predominant in the mineral and base oil; 2) cycloalkanes were predominant in the synthetic and semi-synthetic oils; whereas the branched alkanes were more prominent in the mineral and base oils; 3) for lubricants used for a short period, a slight increase of LMW compounds was observed, while the HMW compounds underwent a decrease, whereas, there was an overall mass reduction for all the aliphatic compounds detected in the oil samples used for six-months.